The Representation of Gender and Sexuality in Michelle Obama's Becoming - Dahal, Radhika Devi (KMC Research Journal, 2024)
This research focuses on the gender and sexuality in Michelle Obama’s Becoming, her autobiographical novel. Obama attempts to present her past and present life in par with her gender role in her life. Although she has talked about many things in the book, her primary focus is on the role of gender and sexuality to shape her career. She has a dual identity as a daughter in her childhood and as a wife in her adulthood. She grows up in a simple family experiencing gender and sexuality in the book in which she feels in the family and the places she is grown up. As she goes to the university, she experiences discrimination between boys and girls. It helps her to address the problems when she is in politics having power to address the domination being a girl. Obama tries to clarify that gender and sexuality exist in every society in one way or another. Sometimes, it depends on people how they create their identity despite the obstacles as she has faced in her life. As Simone de Beauvoir claims 'one is not born a woman, but, rather, becomes one', the socially constructed idea of woman dominates her whole life. Michelle assimilates all the evils of the society and tries to make her identity despite the difficulty.The protagonist of the book is author herself. She has written whatever she has experienced and encountered the problems. To examine the research, the researcher has applied Marin Coleman and John Stuart Mill's ideas of women and their role in society. The significance of the research is to explore the shaping of life of Michelle Obama and gender roles in her career. Obama's point of departure is to show one's internal thoughts, determination and family play key role in addition to gender and sexuality. The study focuses on her personal views on family, community, race and the whole country. As she faces problems being a woman, she remembers her family background and the impact of her childhood environment. She keeps balancing the relationship with her husband. She assists him in every possible way without overshadowing her own distinct identity. Hence, gender and sexuality do not stop women from shaping their identities if they are determined to accomplish something in their life.